Damage to red blood cells during whole blood storage. Issue 2 (August 2020) - Oh, Joo-Yeun; Marques, Marisa B.; Xu, Xin; Li, Jindong; Genschmer, Kristopher; Gaggar, Amit; Jansen, Jan O.; Holcomb, John B.; Pittet, Jean-Francois; Patel, Rakesh P.
Abstract : BACKGROUND: Transfusion with stored whole blood (WB) is increasingly routine practice to resuscitate bleeding trauma patients. Storage of packed red blood cells (pRBC) results in multiple biochemical, structural, and metabolic changes, referred to as to the storage lesion that may mediate adverse effects associated with transfusion of older RBC units. These include increased hemolysis, oxidative stress, and accelerated scavenging of nitric oxide (NO). Whether similar changes occur to stored WB is unclear and are characterized in this study. METHODS: Ten WB units, in citrate-phosphate-dextrose, were purchased from the American Red Cross and changes in hemolysis (increased free hemoglobin, heme, and microparticles), oxidative stress indexed by redox cycling of peroxiredoxin-2 (Prx-2) and NO-scavenging kinetics were determined at different storage times until expiration. RESULTS: Microparticle number and free hemoglobin, but not heme, increased in a storage time-dependent manner. When normalized to the initial number of RBCs in stored WB units, hemolysis rates were similar to those reported for pRBCs. Prx-2 recycling kinetics were slower at expiration compared with earlier storage times. Rates of NO dioxygenation did not change with storage, but were decreased compared with freshly isolated RBCs. CONCLUSION: Storage of WB results in changes associated with the pRBC storage lesion but not for all parameters tested. The relative rate of hemolysis (indexed by free hemoglobin and microparticles) and oxidative stress was similar to that of pRBCs. However, the absolute level of hemolysis products were lower due to lower hematocrit of stored WB units. The clinical significance of these findings requires further investigation.